Student Well-Being of Generation Alpha: A Case Study in An Islamic Elementary School - Choirun Nisa; Muhammad Haidar Husein; Izzati Ramadhani Herry; Choirul Anwar; Mohammad Nasirudin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
This study aims to analyze the student well-being profile of Generation Alpha in the context of Islamic elementary education to map the factors contributing to learning happiness. This research employed a descriptive quantitative approach with a case study design involving 29 fifth-grade students at an Islamic Elementary School in Salatiga. Data were collected using a four-point Likert scale questionnaire and analyzed using descriptive statistics to determine the mean and percentage of achievement. The findings indicate that the overall student well-being is in the “happy” category, with a collective achievement rate of 77% and an average score of 3.04. The highest scores were recorded in “pride in achievement” (3.72) and “meaning of school for the future” (3.66), while “task independence” received the lowest score (2.00). This study concludes that while students feel happy and find meaning in their education, there is a significant need for instructional strategies that foster greater autonomy and self-efficacy.